Two new species of Baetis s. l. (Ephemeroptera, Baetidae) from Yintiaoling Nature Reserve of Chongqing, China - Mu, Pengxu; Huang, Xiaolei (Zootaxa, 2025)
Two new species of Baetis s. l. are described and illustrated based on nymphal materials. Baetis chongqingensis sp. nov. is characterized by the elongated labrum, the presence of stout setae on scape, the absence of apical scale on segment II of maxillary palp, the well-developed projection on segment II of labial palp, and the absence of chagrin and spatulate setae on abdominal terga. Baetis (Rhodobaetis) qianlei sp. nov. can be differentiated from the other species of subgenus Rhodobaetis by the number of spatulate setae on the scape and pedicel, the shape of labial palp and tergalii, and the length of paracercus.